2009
DOI: 10.1002/jmri.21639
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of dobutamine stress cardiovascular magnetic resonance imaging in children

Abstract: Purpose:To evaluate the feasibility of dobutamine stress magnetic resonance (DSMR) in pediatric patients. Materials and Methods:The medical records of all DSMR studies performed on patients Յ22 years old at a single institution were retrospectively reviewed. The DSMR protocol included dobutamine doses up to 40 g/kg/minute and atropine to attain the target heart rate [0.85 ⅐ (220 -age)].Results: Thirty-two DSMR studies were performed in 28 patients (median age ϭ 7.3 years; range ϭ 0.8 -22 years). Twenty of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…Major side effects, such as ventricular arrhythmias or even death, have been described in adult patients with coronary artery disease, receiving high doses of dobutamine of up to 40 μg/kg/min [1,2]. Highdose dobutamine stress imaging is rarely used in children and patients with CHD [13,[28][29][30]. It is usually performed to induce wall motion abnormalities in patients with coronary artery abnormalities [4,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major side effects, such as ventricular arrhythmias or even death, have been described in adult patients with coronary artery disease, receiving high doses of dobutamine of up to 40 μg/kg/min [1,2]. Highdose dobutamine stress imaging is rarely used in children and patients with CHD [13,[28][29][30]. It is usually performed to induce wall motion abnormalities in patients with coronary artery abnormalities [4,13].…”
Section: Discussionmentioning
confidence: 99%
“…Highdose dobutamine stress imaging is rarely used in children and patients with CHD [13,[28][29][30]. It is usually performed to induce wall motion abnormalities in patients with coronary artery abnormalities [4,13]. In both echocardiographic and CMR studies, no major side effects have been reported in pediatric patients using high-dose dobutamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many individuals with CHD undergo CMR for surveillance of CHD and ventricular function and stress sequences may be added to these studies. 27 Since prosthetic patches and conduit insertion sites can be identified by CMR, visualizing the anatomy with high spatial resolution can be helpful for interpretation of CMR stress perfusion by demonstrating which regions of the heart are not expected to perfuse. Coronary microvascular dysfunction can be assessed with rest and vasodilator stress gadolinium-enhanced CMR imaging.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…This "biphasic response" ence in the pediatric population is more limited, but the available data are encouraging. 11 There are now CMR-compatible ergometers that allow for cardiac functional assessment during exercise. 12 One of the strengths of CMR is its ability to evaluate tissue characteristics.…”
Section: Stress Echocardiographymentioning
confidence: 99%